2018
DOI: 10.1021/acs.jpcc.8b03815
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Partial Crystallization on the Dynamics of Water in Mesoporous Silica

Abstract: We use differential scanning calorimetry, broadband dielectric spectroscopy, and deuteron nuclear magnetic resonance to investigate water dynamics in MCM-41 pores with a diameter of d = 2.5 nm. At high pore fillings, partial crystallization at T m = 221 K leads to a dynamic crossover. The reorientation of all water molecules shows non-Arrhenius temperature dependence above 221 K, while two Arrhenius processes associated with liquid and crystalline water species can be distinguished below this temperature. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
80
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(97 citation statements)
references
References 71 publications
(170 reference statements)
17
80
0
Order By: Relevance
“…More precisely, the relaxation processes of confined liquids showed a broadening on the low-frequency flank, which did not occur for the processes of bulk liquids. This broadening was mainly caused by slow molecules near the confining walls [ 32 , 44 , 76 ], as was anticipated in core-shell models and confirmed in systematic filling-level and solvation-level dependent studies on neat confined liquids [ 65 , 77 , 78 , 79 ]. Here, the CC distribution is used to phenomenologically consider this effect for the confined solutions, while the Cole-Davidson distribution proved to be useful to describe the process of glass-forming bulk liquids.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…More precisely, the relaxation processes of confined liquids showed a broadening on the low-frequency flank, which did not occur for the processes of bulk liquids. This broadening was mainly caused by slow molecules near the confining walls [ 32 , 44 , 76 ], as was anticipated in core-shell models and confirmed in systematic filling-level and solvation-level dependent studies on neat confined liquids [ 65 , 77 , 78 , 79 ]. Here, the CC distribution is used to phenomenologically consider this effect for the confined solutions, while the Cole-Davidson distribution proved to be useful to describe the process of glass-forming bulk liquids.…”
Section: Resultssupporting
confidence: 62%
“…Two relaxation processes with similar properties were observed for neat hydrogen-bonded liquids in silica confinement [ 33 , 86 , 88 , 97 , 98 ]. While they were interpreted in terms of core-shell models for confined alcohols [ 33 , 97 ], they were attributed to coexisting liquid and solid phases or high-density and low-density liquid phases for confined water [ 78 , 86 , 98 ]. In our case of binary mixtures, another possible explanation resulted from the finding that preferential interactions with the pore walls could lead to microphase separation and, thus, to bimodal dynamics [ 28 , 29 , 40 , 43 , 44 , 99 , 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…strong) behavior upon cooling 11,12 . As recently noted by Lederle et al 34 , with progressive freezing of nanoconfined water from the center towards the pore wall, the remaining liquid fraction becomes increasingly confined by the surrounding. This confinement is expected to be particularly severe in smaller pores.…”
Section: Freezing Kinetics Of Nanoconfined D 2 O From 2 H Wideline Nmmentioning
confidence: 64%
“…Figure 4 shows temperature-dependent correlation times τ obtained from 2 H NMR approaches to water reorientation in mesoporous silica. Clearly, there is a dynamic crossover near 220 K. Combining this NMR analyses with DSC and BDS studies [ 215 ], it turned out that, for a pore diameter of 2.8 nm, the dynamic crossover occurs near the melting temperature T m so that liquid and crystalline water fractions with, respectively, faster and slower rotational dynamics coexist inside the pores below this temperature (see Figure 4 a). It was concluded that partial crystallization causes the effect, explicitly, that the dynamics of water changes when ice forms and further restricts the accessible pore volume.…”
Section: Simple Liquids In Confinementmentioning
confidence: 93%
“…To tackle this problem, 2 H NMR was used to investigate reorientation dynamics of unfreezable water (D 2 O) in MCM-41 and SBA-15 pores over wide temperature ranges towards the glass transition [ 45 , 176 , 181 , 183 , 213 , 214 , 215 , 216 , 217 , 218 , 219 ]. In particular, spin-lattice relaxation, line-shape analysis, and stimulated-echo experiments were combined to ensure broad dynamic ranges and the pore-size was systematically varied to study possible finite-size effects.…”
Section: Simple Liquids In Confinementmentioning
confidence: 99%